2020
DOI: 10.1172/jci.insight.138873
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine deiminase 2 has potential as both a biomarker and therapeutic target of sepsis

Abstract: Peptidylarginine deiminases (PADs) are a family of calcium-dependent enzymes that are involved in a variety of human disorders, including cancer and autoimmune diseases. Although targeting PAD4 has shown no benefit in sepsis, the role of PAD2 remains unknown. Here, we report that PAD2 is engaged in sepsis and sepsis-induced acute lung injury in both human patients and mice. Pad2 –/– or selective inhibition of PAD2 by a small molecule inhibitor increased survival and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…As expected, the employment of a selective PAD2 inhibitor in the same model of LPS-induced endotoxic shock significantly increased survival (70). Thereafter, our studies further demonstrated that the knockout of Pad2 can improve survival in CLP-induced sepsis and PA-sepsis (59,103). Therefore, it can be inferred that PAD2 likely acts as a critical mediator in the pathogenesis of sepsis.…”
Section: Infections Sepsissupporting
confidence: 80%
“…As expected, the employment of a selective PAD2 inhibitor in the same model of LPS-induced endotoxic shock significantly increased survival (70). Thereafter, our studies further demonstrated that the knockout of Pad2 can improve survival in CLP-induced sepsis and PA-sepsis (59,103). Therefore, it can be inferred that PAD2 likely acts as a critical mediator in the pathogenesis of sepsis.…”
Section: Infections Sepsissupporting
confidence: 80%
“…Hypercitrullination in synovial fluid and anti-citrullinated protein antibodies in plasma are found in rheumatoid arthritis [ 44 ], suggesting that the hypercitrullinated molecules may serve as autoantigen. PAD2 and PAD4 are potential biomarkers and therapeutic targets of sepsis [ 45 ]. PAD4 inhibitor block neutrophil extracellular trap formation [ 46 ], reducing bleomycin fibrosis [ 47 , 48 ].…”
Section: Neutrophils In Immunitymentioning
confidence: 99%
“…Here, we constructed the sepsis model of C57BL/6 mice by the use of LPS, and the symptoms of ALI were noticed in the model. The first mock exam has been widely used in the pathogenesis and drug screening of sepsis induced acute lung injury [18]. This animal model has several advantages, such as simple steps and no inoculation [18].…”
Section: Discussionmentioning
confidence: 99%
“…The first mock exam has been widely used in the pathogenesis and drug screening of sepsis induced acute lung injury [18]. This animal model has several advantages, such as simple steps and no inoculation [18]. Additionally, it could also induce the animal to produce a large number of cytokines, similar to that in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation